Identifying primary immunodeficiency through the evaluation of severe, persistent, unusual, and recurrent infections in Indonesian children - Muktiarti, Dina; Hendarto, Aryono; Munasir, Zakiudin; Wulandari, Dewi; Satari, Hindra Irawan; Werdhani, Retno Asti; Kumara Wati, Ketut Dewi (Paediatrica Indonesiana, 2026)
Background Primary immunodeficiency (PID) is widely underdiagnosed in countries with high rates of infection and limited diagnostic facilities, such as Indonesia. It remains challenging to distinguish PID from other conditions predisposing children to severe, persistent, unusual, and recurrent (SPUR) infection. Such conditions include secondary immunodeficiency caused by human immunodeficiency virus (HIV) infection, allergic diseases, and chronic diseases with structural or anatomical abnormalities. Objective To evaluate children with SPUR infections for PID and to compare the clinical characteristics of children with PID to those with other underlying conditions. Methods We conducted a cross-sectional, analytic study of children aged 0-18 years presenting with SPUR infections at 10 hospitals in Jakarta, Indonesia, from July 2024 to September 2025. Clinical assessment and laboratory investigations, including immunological tests, were performed to identify the underlying cause of SPUR infections. Children were classified as healthy, PID, secondary immunodeficiency (HIV), allergy, or chronic disease/anatomical abnormalities. Results Two hundred fifty-four subjects (53% male) with a median age of 26 months were included in our study. Most of them had a history of pneumonia (72.1%), diarrhea (31.1%), and pulmonary tuberculosis (27.9%). Thirty-three (13%) subjects were diagnosed with PID, with the majority being male (60.6%). The most common PID found was antibody deficiency (27.3%), followed by immunodeficiencies combined with associated or syndromic features (24.2%), and immunodeficiencies affecting cellular and humoral immunity (21.2%). Median age of onset in the PID group was 12 (3–24) months. Severe malnutrition was most common in children with HIV. Gender, parental consanguinity, and adverse events following live vaccines did not differ significantly across groups. Conclusion The prevalence of PID among children with SPUR infection in this study was 13%, with the most common classification being antibody deficiency.